Analysis on market participation by public institutions - Park, Jin (The Korea Institute of Public Finance SeoulKR, 2013)
Aims to investigate the role of public institutions in the market, under consideration of direct or indirect competition iwth private enterprises; as an instrument to achieve policy objectives; and to generate funds.